Reno-protective effect of angiotensin converting enzyme inhibitor and angiotensin II receptor blockers in type 2 diabetic nephropathy with elevated urine albumin to creatinine ratio - Vankayala, Ashok; Mantha, Karuna Sagar; B. H. V. K., Praveen Varma; Sayana, Suresh Babu; D. S. S. K., Raju (International Journal of Advances in Medicine, 2019)
Background: Nephropathy is responsible for an End Stage Renal Disease (ESRD) in type 2 diabetics if uncontrolled. The monotherapy/combination of Angiotensin Converting Enzyme inhibitor (ACEi) and Angiotensin II Receptor Blockers (ARBs) can retard the progression of urine albumin to creatinine ratio in diabetic nephropathy but, the data shows an inconsistency in the efficacy of these drugs. So, the present study was aimed at comparing the reno-protective effect of ACEi/ARBs in type 2 diabetics. Methods: A prospective, randomized study is conducted at Maharaja’s Institute of Medical Sciences, Nellimarla, Vizianagaram, Andhra Pradesh, India with 100 patients, who are randomly categorised and equally distributed among the two groups and treated with Enalapril (ACEi) and Losartan (ARBs) for 6 months. 24-hour urine albumin to creatinine ratio and HbA1c are recorded before and after the treatment. Results: Enalapril and losartan showed a non-significant reduction in urine albumin to creatinine ratio from 196.2±17.5 to 185.9±15.2 (p=0.66) and 236.8±16.3 to 193.7±20.6 (p=0.11) respectively. A strict glycemic control has shown a reduction in HbA1c in both the groups. Conclusions: Present findings suggested that losartan is relatively more effective than enalapril in reducing the 24-hour urine albumin to creatinine ratio of diabetic nephropathy patients. Along with these drugs, regulation of blood glucose will assist in retarding the progression of nephropathy in type 2 diabetics.